Tolerance of Islam, Christianity, and Hinduism in a Plural Society - Subakri, Subakri; Saihan, Saihan (Didaktika Religia, 2023)
This study is to determine and identify the implementation of the concept of understanding tolerance in the plurality of people of Kedungrejo Village, Rowokangkung District, Lumajang Regency. The village community is a society with a very high level of plurality; various religious cultures and feelings exist in the village. However, harmony and mutual respect are evident in everyday life. Differences are not a reason for the village community to be hostile to each other, but differences are considered wealth to be grateful for. So, in some ways, the village community carries out activities and life together regardless of the differences that exist. The approach used in this study is qualitative. The paradigm is phenomenological or interpretive. A qualitative approach is a paradigm of Natural Research, which is to find a theory by pulling it from the beginning of nature, that is, from data that comes from the real world. The researchers took the research location in Kedungrejo Village, Rowokangkung district, Lumajang Regency. The results of this study show that all religions tend to have claims of absolutism, whether Islam, Christianity, Hinduism, or Judaism. Claims of monotheism that are particularist-subjective will impact inter-religious conflict, and the competition will be heightened if several strong and particularistic religious organizations coexist.